2008
DOI: 10.1007/s11062-008-9021-8
|View full text |Cite
|
Sign up to set email alerts
|

The lagena (the third otolith endorgan in vertebrates)

Abstract: In this review, the structure and functions of the lagena (the third otolith organ) in an evolutionary lineage of the vertebrates are described and discussed. The lagenar macula appears first in the posterior part of the sacculus of elasmobranchs; in these animals, the lagena is considered to be involved in the balance support (orientation with respect to the gravitation force). The lagena as a separate endorgan has been described in teleost fishes; in some species, the lagena is connected with the sacculus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…The lagena may play a similar role in sensing gravitational and acceleration signals as the utricle does. Current evidences from morphological and anatomical studies [8,11] indicate that the avian lagena mainly sends neural projections to the vestibular nuclei and the cerebellum, and at an obviously lesser extent to the auditory nuclei. It is also reported that lagenal hair cells are insensitive to sound signals [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lagena may play a similar role in sensing gravitational and acceleration signals as the utricle does. Current evidences from morphological and anatomical studies [8,11] indicate that the avian lagena mainly sends neural projections to the vestibular nuclei and the cerebellum, and at an obviously lesser extent to the auditory nuclei. It is also reported that lagenal hair cells are insensitive to sound signals [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The macula lagena is another otolithic organ in the inner ear in non-mammalian vertebrates [7] and has distinct functions across species [8] . In the fish, the lagena is mainly involved in sensations of acoustic oscillations and orientation in the vertical plane.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the vestibular system in vertebrates is, from the evolutionary aspect, rather conservative, otolith endorgans in different animals demonstrate certain variability [1][2][3]. In most mammals, two otolith endorgans, the utriculus and the sacculus, are found, while in many vertebrates of other classes there is the third otolith endorgan (called the lagena).…”
Section: Introductionmentioning
confidence: 99%
“…In most mammals, two otolith endorgans, the utriculus and the sacculus, are found, while in many vertebrates of other classes there is the third otolith endorgan (called the lagena). The receptor apparatus of the lagena includes a group of hair sensory cells localized in a certain cavity (chamber) of the membranous labyrinth of the inner ear and covered by the otoconium membrane [1][2][3]. Among vertebrates, the lagena as an independent endorgan was described for the first time in elasmobranch cartilaginous fishes (sharks and rays) [4] in which this structure is considered to be the equilibrium organ [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation